Damages for personal injuries and causing death resulting from road traffic accident: A survey from Malaysia - Ismail, S.Z.; Khalil, S.A.; Al-Mekhlafi, A.M.A.S.; Samudin, S.A. (2017)
In Malaysia, damages for personal injuries and causing death, other than homicide, is primarily governed by the Civil Law Act 1956 (Amendment 1984). Quantum for damages for personal injuries are said to be higher that the fatal case which is confined to bereavement, funeral expenses, estate claimand dependency claim. If the injured are alive and suffer resulting from the incident, there are four types of damages that tan. be claimed, namely: (i) pain and suffering and loss of amenities, (ii) loss of future earnings, (iii) loss of.earning capacity and (iv) future care expenses. For most road accident cases, the root cause is said. to be negligence. TIle principles of negligence under the law of tort is used to determine liability. Using road. traffic accident cases as the focus of the study. this paper examines in I details the current situation, address issues, the role of insurance company as well as show where changes to the law are necessary.